English as an International Language: Issues and Implications - Jack C. Richards (Journal of Pedagogical and Teacher Professional Development, 2026)
This paper explores the complexities and implications of English as an International Language (EIL), emphasizing its evolving role beyond native-speaker contexts and its significance within language education. Drawing on frameworks such as Kachru’s three-circle model and concepts of World Englishes, it examines how English functions differently across inner, outer, and expanding circle countries. The article investigates issues surrounding dialects, varieties, standards, and the impact of globalization on English usage and teaching. It highlights the need for intercultural competence and critically examines traditional pedagogical norms that prioritize native-speaker models. Ultimately, it argues for a paradigm shift in English language pedagogy toward recognizing localized, pluralistic forms of English and promoting communicative competence over native-like accuracy. These insights have profound implications for curriculum design, teacher education, and instructional materials in global English language teaching.